A method for photo-identification of turtles of the Phrynops williamsi species - Bertoldi, Guilherme; Hoppe, Aurélio (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA), 2020)
This paper presents a method for photo-identification of Phrynops williamsi turtles. This identification is performed using shape descriptors which computationally represent the horseshoe-shaped and circular-shaped bands that can be found on the ventral surface of the turtle's head. The input image is converted to grayscale, binarized, filtered with morphologic operations, segmented based on the contours of the object and the components are selected based on their geometric characteristics. With the extraction of these characteristics, the method calculates de Fourier Descriptors and create a unique identifier used to identify the turtle from the input image. Results show that the presented method has reached a success rate of 85.71% in intra-class comparison and 85.17% in inter-class comparison.